Content-based instruction in an english oral communication course at the University of Costa Rica - Annabelle Hernández Herrero (Universidad de Costa Rica, 2005)
This article presents the results of a research study carried out with a group of second-year English students at the School of Modern Languages at the University of Costa Rica. The purpose of this investigation was a) to find out if the recycling of content through the use of a variety of authentic informational sources (readings, videos, brochures, newspapers, movies, lectures, etc.) contributes to the improvement of the students' oral production skills, b) to identify which tasks best promote the oral participation of the students, c) to determine how to integrate the teaching of pronunciation into everyday classroom activities and d) to determine which linguistic aspects have to be reinforced to improve the students' accuracy and fluency in oral production tasks.    El artículo que se ofrece consiste en una comparación etnográfica sobre propuestas educativas no formales, entre el Museo de los Niños de Costa Rica y seis museos o centros de ciencia españoles ubicados en lo que se conoce como la nueva museología. Se detallan los aspectos de la nueva museología española que pueden enriquecer la práctica del museo costarricense.